2008
DOI: 10.1097/scs.0b013e31815c8aae
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis

Abstract: Differing types of fixation, diagnosis of syndrome, and multiple-suture craniosynostosis were statistically correlated to increased reoperative rates. Age at initial operation and sex were not correlated to increased reoperative rates. Finally, this institution's complication and reoperative rates compare with other published results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 10 publications
0
25
1
2
Order By: Relevance
“…In later years, surgery consisted of various methods of craniotomy and remodeling that are still the most frequently applied technique [10,24,25,26]. Distraction osteogenesis was introduced in the mid- to late-1990s, and appeared to offer advantages in that: bone fusion is more effectively accomplished, the operation time is shortened, and transfusion volume is decreased [2,3,4,7,9,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In later years, surgery consisted of various methods of craniotomy and remodeling that are still the most frequently applied technique [10,24,25,26]. Distraction osteogenesis was introduced in the mid- to late-1990s, and appeared to offer advantages in that: bone fusion is more effectively accomplished, the operation time is shortened, and transfusion volume is decreased [2,3,4,7,9,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The mean operation times for classical craniotomy/remodeling and distraction osteogenesis have been reported to range from 150 to 441 and from 183 to 336 min, respectively, and the mean volume of transfused blood ranged from 100 to 426 and 178 to 350 ml, respectively, indicating a high risk for children undergoing classical craniotomy and remodeling [3,4,6,9,11,12]. Although there are few reports to date which have described repeat surgery after distraction osteogenesis, it has been indicated that repeat surgery occurs in 6.7–40% of patients who received classical craniotomy and remodeling, and therefore a new and effective surgical method is necessary [10,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goals of craniosynostosis treatment are to expand the intracranial volume, to protect the eyes, to restore upper airway patency, and to improve cosmesis (Pearson et al, 2008;Scott et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The primary goals for surgical correction are to expand the intracranial volume, thereby allowing for unimpeded cerebral growth whilst improving the aesthetic appearance of the child [2]. DO in synostotic plagiocephaly offers the advantages of a decreased perioperative morbidity, less soft tissue envelope restriction of expansion, and the correction of cranial base angulation [3].…”
Section: Introductionmentioning
confidence: 99%